Pengaruh Budaya Kolaborasi dan Keterlibatan Mahasiwa pada Feasibility Project Study terhadap Tingkat Kepuasaan Mahasiswa, Dimediasi oleh Kinerja Hasil - Kusumawati, Heni (LPPM STIE YKPN Yogyakarta, 2024)
This study aims to obtain empirical evidence of the impact of Collaboration Culture and Student Involvement on Satisfaction Levels in Project Based Learning, with Net Benefit as a mediating factor. The object of the research is students who take Business Feasibility Studies courses at universities in Yogyakarta. The number of research samples was 100 respondents of final semester students who took the Business Feasibility Study course. The research methodology with the multivariate statistical analysis method was developed from regression and analysis of the Structural Equation Modeling (SEM) path. Based on the results of data processing, the Average Variance Extracted (AVE) value of all variables is above 0.5 and the Cronbach's alpha value is above 0.7, meaning that the data is valid and reliable. Based on the classical assumption test in this study, there is no problem of multicollinearity of normally distributed data. This study found that collaboration culture has no effect on the achievement of results, while student involvement has an effect on the performance of results in project completion. Meanwhile, the performance of the results is getting higher, encouraging the level of student satisfaction in the implementation of the Business Feasibility Study project. The role of Performance Results (Net Benefit) mediates the influence of student involvement in achieving the satisfaction level. Meanwhile, the influence of the variable relationship of Collaboration on Satisfaction Level does not involve the role of Performance Results.